Mekanisme Pasar Dalam Islam : Tinjauan Sejarah - Muhammad Muhammad (Millah: Journal of Religious Studies, 2002)
The article attempts to analyze the concept of market mechanism in Islamic view as developed by the Muslim scholars. The ideas of Muslim scholars are at large remained unexplored who had offered rather detailed and sophisticated discourse on market and pricing mechanism. Our study is confined to the ideas of following representative personalities such as Abu Yusuf al Ghazali, Ibn Taimiyah, and lbn Khaldun. The article concludes with the note that considerable ideas on the market and prizing mechanism were found with the Muslim scholars long before the mid eighteenth century, and that the views of Islamic writers were far detailed and clear. This requires reconsideration on Shumpeter's statement about mechanism of prizing that nothing worth mentioning existed before the middle of eighteenth century. Especially, the contribution of the Arab-Islamic scholars to economic thought be rehabilitatedin the science of economics for the sake of doctrinal continuity as well as objectivity.